As construções recíprocas nos textos portugueses arcaicos. Um subsistema gramatical em vias de surgimento - Nkollo, Mikołaj (Studia Romanica Posnaniensia, 2013)
The main goal of this paper is to identify various methods of expressing reciprocity encountered in Old Portuguese texts (from 13th to 15th centuries) and to account for putative evolutionary mechanisms conducive to their emergence and their subsequent shape. Most of the grammaticalization pathways documented in human languages have been implemented in Old Portuguese, as well. Only syntactically built reciprocals will be taken into account; their lexical counterparts, where reciprocity is an inherent semantic property, will be evoked incidentally. Peculiar characteristics exhibited by ancient Portuguese reciprocal constructions comprise: a shaky selection of determiners distributed over the bipartite indefinite "um ao outro" and its varieties, a rather peripheral, though clearly distinct exponent "d’huũa parte e d’ooutra" designed to highlight a twofold (and not manifold) internal structure of states of affairs, a remarkable mobility of "se" and, finally, a blurred distinction between "entre eles" (preferably anaphoric) and "entre si" (used seemingly at random, with either indefinite and definite objects). Compared to other incipient Romance languages, a system built around this set of markers was rather scanty. It relied on numerous makeshift solutions, as typically do the languages whose particular grammatical areas are merely on the point of coming into existence.